The Effectiveness of LenshookeTM Semen Quality Analyzer X1 Pro for Human Semen - Agustinus Agustinus; Supardi Supardi; Pety Narulita; Budiono Budiono (Indonesian Andrology and Biomedical Journal, 2020)
Background: LenshookeTM Semen Quality Analyzer (SQA) X1 Pro is an automated semen analysis. The accuracy of LenshookeTM SQA X1 Pro has never been analyzed with World Health Organization (WHO) standard method. Aim: This study aims to examine whether the LenshookeTM SQA X1 Pro method provides reliable results according to the WHO standard method. Methods: This study was a laboratory analytic observational study using 60 patients in Andrology clinic of Dr. Soetomo Hospital. The concentration, progressive motility (PR), total motile sperm count (TMSC), and morphology results of the LenshookeTM SQA X1 Pro and standard method were analyzed statistically using correlation, Bland Altman, and diagnostic test. Results: Significant correlation between two methods were found in all parameters (concentration: r = 0,970; PR: r = 0,781; TMSC: r = 0,952; morphology: r = 0,568). The mean difference for concentration, PR, TMSC, and morphology between the two examination methods were 1,165 million/ml, 7,05%, 7,584 million/ejaculate, and 2,25%. However, it found that the correlation and agreement were weaker in sample with low number of spermatozoa per high power field. The results revealed a sensitivity of 100%, 81%, and 59% for oligozoospermia, astenozoospermia, and teratozoospermia, respectively. The specificities were shown to be 100%, 74%, and 100% for oligozoospermia, astenozoospermia, and teratozoospermia, respectively. Conclusion: The LenshookeTM SQA X1 Pro gives a reliable result for determining oligozoospermia and asthenozoospermia, but in the situation that the clinicians need the accurate data, standard method should be used.